Cold-Water Soft Corals (Cnidaria: Nephtheidae) as Habitat for Juvenile Basket Stars (Echinodermata: Gorgonocephalidae) - Neves, Bárbara de Moura; Wareham Hayes, Vonda; Herder, Erin; Hedges, Kevin; Grant, Cindy; Archambault, Philippe (Frontiers in Marine Science, 2020)
Nephtheidae soft corals are a common component of benthic ecosystems in the Northwest (NW) Atlantic and in the Arctic, but little is known about their functional roles. Here we investigated their role as habitat for basket stars (Ophiuroidea). By examining over 4500 soft coral colonies of Drifa glomerata, Duva florida, Gersemia spp., and Pseudodrifa racemosa collected during trawl surveys in the regions of Newfoundland, Labrador and West Baffin Bay, we show that Nephtheidae soft corals are habitat for juvenile Gorgonocephalus sp. basket stars. Juvenile Gorgonocephalus sp. were found on all soft corals species, but Drifa glomerata was the soft coral species with the highest occurrence of associated juvenile basket stars (32%), with a maximum of 111 basket stars found on a single 4.8 cm tall (contracted state) colony. Individual basket star disc diameter did not change with colony height, but it varied with season for individuals found on D. glomerata. On the other hand, colony height was positively related with maximum disc diameter (D. glomerata), and presence and number of basket stars on a colony (D. glomerata and D. florida). One very young ophiuroid was found within one polyp of a D. florida colony collected in July. We also examined bottom trawl survey data from 2011-2017 from Newfoundland to Baffin Bay, and other locations in the Eastern Canadian Arctic and found that for our largest database, 45% of trawl sets that contained basket stars also contained corals, of which 67% were Nephtheidae soft corals. In this study we show that all four Nephtheidae soft coral taxa studied act as habitat for juvenile basket stars, which are conspicuous components of benthic communities in cold-water environments. Soft corals are commonly exposed and vulnerable to bottom fishing gear in the North Atlantic. We urge future studies evaluating the nature of this relationship, the potential role of soft corals as nurseries, and the potential degree of dependency/preference between basket stars and soft corals in relation to other organisms.